Outdoor Activity in the Daytime, but Not the Nighttime, Predicts Better Mental Health Status During the COVID-19 Curfew in the United Arab Emirates - Al Anouti, Fatme; Thomas, Justin; Karras, Spyridon; El Asswad, Nour (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic and the associated infection prevention and control measures had a negative impact on the mental health of many people. In the United Arab Emirates (UAE), infection control measures implemented after March 24th, 2020, placed necessary restrictions on people's freedom of movement. Aim This study aimed to assess the association between levels of daytime vs. nighttime outdoor activity and mental health among a sample of UAE residents during the lockdown period. Method An opportunity sample of 245 participants completed an online survey assessing levels of depression, somatic symptoms, daytime and nighttime activity levels. Results Multivariate logistic regression revealed that daytime activity, but not nighttime activity, was associated with a lower risk of clinically significant depressive and somatic symptomatology. Conclusion The association of better mental health with daytime not nighttime outdoor activity could be possibly attributed to vitamin D, but further studies are needed to confirm this speculation.